Group Theory In Molecular Symmetry - et. al., Jita Dutta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Symmetry is one of the most pervasive concepts in the universe. It is used in our everyday language in two meanings. In the one sense symmetry means something like well-proportioned, well-balanced and the other sense. Symmetry denotes the sort of concordance of several parts by which they integrate into a whole. The study of symmetry provides one of the most appealing applications of group theory. The systematic mathematical treatment of symmetry is called group theory. Group theory is a rich and powerful subject by which we shall confine our use of it at this stage classification of molecules in terms of their symmetry properties, the construction of molecular orbitals and the analysis of molecular vibrations. To make the idea of molecular symmetry as useful as possible we must develop some rigid mathematical criteria of symmetry. Group theory is the tool by means of which generalizations concerning molecular symmetry are applied. In the advanced study of inorganic chemistry a systematic study of symmetry and the ways of specifying it with mathematical precision are important because wide variety of symmetric structure encounted.